2014
DOI: 10.1111/jace.13091
|View full text |Cite
|
Sign up to set email alerts
|

Eu‐Doped β‐SiAlON Phosphors: Template‐Assistant Low Temperature Synthesis, Dual Band Emission, and High‐Thermal Stability

Abstract: A hard template route has been successfully developed for synthesis of b-SiAlON:Eu phosphors at low temperatures. The synthesis utilizes mesoporous silica (SBA-15) skeleton as an active Si source, combined with the carbothermal reduction and nitridation method. It has been shown that the additional driving force from high surface area and porosity of SBA-15 enables b-SiAlON:Eu (with compositions ofxEu, x = 0.010-0.200 and z = 1.000) phosphors to be formed as a dominant phase at low temperature of 1400°C. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The low Eu 2+ concentrations would cause the β-SiAlON:Eu phosphors to have a blue emission and the high Eu 2+ -doping concentrations would cause the β-SiAlON:Eu phosphors to have a green emission [13]. Zambare and Murthy adopted a standard solid-state reaction method to investigate the properties of Eu-doped YPVO 4 , Y 2 O 3 , and YLaVO 4 phosphors [14].…”
Section: Introductionmentioning
confidence: 99%
“…The low Eu 2+ concentrations would cause the β-SiAlON:Eu phosphors to have a blue emission and the high Eu 2+ -doping concentrations would cause the β-SiAlON:Eu phosphors to have a green emission [13]. Zambare and Murthy adopted a standard solid-state reaction method to investigate the properties of Eu-doped YPVO 4 , Y 2 O 3 , and YLaVO 4 phosphors [14].…”
Section: Introductionmentioning
confidence: 99%
“…While the uncommon blue emission at 470 nm has been found in the β-SiAlON compositions having a higher Al content and it was supposed to relate to the local fluctuation of the O/N ratio caused by more Al-O bonds substituting Si-N bonds in SiAlON compositions [4,23]. In our previous research [19], the blue emission was also found in Eu-doped β-SiAlON phosphors prepared via a hard template assistant route, in which the Eu 2 þ content is less than 2.5 at%.…”
Section: Luminescent β-Sialon:eu Fibersmentioning
confidence: 87%
“…According to our previous work on β-SiAlON powder fabrication via carbothermal reduction nitridation (CRN) processing, sucrose (C 12 H 22 O 11 , high molecular weight 342) is a highly active agent to catalyze the nitridation of precursors [18,19]. Therefore, the sucrose was selected as a reducing agent in our electrospinning experiments.…”
Section: Effect Of Sucrose On β-Sialon Phase Formationmentioning
confidence: 99%
“…High temperature is usually required for SSR because the raw material Si 3 N 4 has low diffusion coefficient for reaction, and reducing gases (e.g., NH 3 , CH 4 , or N 2 –H 2 ) are essential in GRN to remove oxygen in raw materials partially or completely. On the other hand, it is more facile for CRN which only uses carbon as reductant . The disadvantage of CRN, however, is that the residual carbon cannot be removed completely so that the emission intensity and absorption efficiency of phosphors are low.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is more facile for CRN which only uses carbon as reductant. 10 The disadvantage of CRN, however, is that the residual carbon cannot be removed completely so that the emission intensity and absorption efficiency of phosphors are low. Here, we develop a novel SiC reduction method to synthesize silica-based oxynitride phosphors without residual carbon problem and the SiC reduction is more tolerant to experimental conditions.…”
Section: Introductionmentioning
confidence: 99%